Altered serum copper homeostasis suggests higher oxidative stress and lower antioxidant capability in patients with chronic hepatitis B. Issue 24 (June 2018) - Huang, Yansong; Zhang, Yuan; Lin, Zhexuan; Han, Ming; Cheng, Hongqiu
Abstract : Abstract: Copper homeostasis can be altered by inflammation. This study aimed to investigate the alteration of serum copper homeostasis and to explore its clinical significance in patients with chronic hepatitis B (CHB). Thirty-two patients with CHB and 10 aged- and sex-matched healthy controls were recruited. Analyses included serum levels of total copper (TCu), copper ions (Cu + ), small molecule copper (SMC), ceruloplasmin (CP), Cu/Zn superoxide dismutase 1 (SOD1), urinary copper, and the activities of serum CP and SOD1. The serum TCu and urinary copper levels in patients with CHB were significantly higher than the controls ( P = .04 and .003), while the serum Cu + was lower than the controls ( P = .0002). CP and SOD1 activities in the serum were significantly lower in patients with CHB compared to controls ( P = .005) despite higher serum concentrations. In addition, serum alanine aminotransferase inversely correlated with serum CP activity ( P = .0318, r = −0.4065). Serum copper homeostasis was altered in this cohort of patients with CHB. The results suggest increased oxidative stress and impaired antioxidant capability in patients with CHB, in addition to necroinflammation. These results may provide novel insights into the diagnosis and treatment of patients with CHB.